Symmetry (Group Theory) and Mathematical Treatment in Chemistry - Akitsu, Takashiro (IntechOpen, 2018)
The aim of this book Symmetry (Group Theory) and Mathematical Treatment in Chemistry is to be a graduate school-level text about introducing recent research examples associated with symmetry (group theory) and mathematical treatment in inorganic or organic chemistry, physical chemistry or chemical physics, and theoretical chemistry. Chapters contained can be classified into mini-review, tutorial review, or original research chapters of mathematical treatment in chemistry with brief explanation of related mathematical theories. Keywords are symmetry, group theory, crystallography, solid state, topology, molecular structure, electronic state, quantum chemistry, theoretical chemistry, and DFT calculations.